Pemenuhan Hak Konstitusional Penghayat Kepercayaan Parmalim Dalam Dokumen Administrasi Kependudukan : Studi Putusan Mahkamah Konstitusi Republik Indonesia Nomor 97/PUU-XIV/2016 - Daulat Nathanael Banjarnahor; Faisal Akbar Nasution; Mirza Nasution; Afnila Afnila (Universitas Sumatera Utara, 2019)
Abstract. The Indonesian Constitution, the 1945 Constitution has regulated the freedom of every citizen to embrace religion or adhere to faith and be treated equally and not discriminatory. In its implementation, freedom to adhere to beliefs, equal treatment and non discrimination has not been felt by believers, especially those who believe in parmalim because they have not been able to state their status as trustees in the demography administration document. The problem in this thesis study is how the legal arrangement related to the Indonesian belief in Indonesia during the new Order period to date, how the implementation of the constitutional rights of the termination of trust Parmalim in the administration The population before and after the Republic Indonesia Constitutional Court Decision Number 97/PUU-XI/2016, and how the State responsibility in fulfilling the constitutional rights of the Parmalim belief in the Demography Administration. This thesis uses empirical legal research methods. The data used in this thesis research are secondary data in the form of primary, secondary, and tertiary legal materials and supported by primary data in the form of in depth interviews with informants. The development of regulations related to belief groups in the New Order era can be seen in several forms of legislation, including the MPR Decree. Other arrangements in the form of a Presidential Decree, Minister of Religion Decree, Minister of Home Affairs Circular, Attorney General's Decree, and Law. During the regulatory reform period, the belief group was in the form of acknowledgment to the belief group which was regulated in the MPR Decree and Law. The implementation of fulfillment of the constitutional rights of the parmalim trustees in demography administration before the Republic Indonesia Constitutional Court Decision Number 97/PUU-XI/2016 was done by the Medan City Demography and Civil Registry Service is limited to Family Cards (KK) and was not done yet to identification card because refer to Demography Administration Law. After the Republic Indonesia Constitutional Court Decision Number 97/PUU-XIV/2016, Slowly gradually the Indonesian state through the government began to take strategic measures to accommodate the inclusion of the status of the belief in the administration of their residency, which is to publish The regulation of the minister of home affair, make any changes to the demographic information system, and issued a circular letter ministry of home affairs’ circular letter. The form of state responsibility in fulfilling the constitutional rights of the people who believe in parmalim in demography administration has not been fully implemented because it is still limited to filling in the KK religious column. Keyword: compliance, constitutional rights, parmalim trustees, demography administration